1983
DOI: 10.1073/pnas.80.9.2594
|View full text |Cite
|
Sign up to set email alerts
|

Soybean nodulin genes: Analysis of cDNA clones reveals several major tissue-specific sequences in nitrogen-fixing root nodules

Abstract: Plant gene products that could play a role in the process of symbiotic nitrogen fixation in leguminous plants were detected by screening a cDNA library prepared from soybean nodule poly(A)+ RNA. About 13% of the 5,700 clones screened contained sequences detectable with a root cDNA probe while about 2,100 clones (37% of the library) contained sequences that were detectable only with nodule cDNA. Five unique sequence species, accounting for more than half of the 2,100 nodule-specific clones, were identified by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 23 publications
0
55
1
Order By: Relevance
“…Class II includes enzymes responsible for the assimilation of nitrogen (9). Among the other enzymes involved in purine catabolism, the specific activities of 5'-nucleotidase, purine nucleosidase and xanthine dehydrogenase have been shown to be significantly higher in root nodules than in uninfected roots (7, some activity of these enzymes within this organelle.…”
mentioning
confidence: 99%
“…Class II includes enzymes responsible for the assimilation of nitrogen (9). Among the other enzymes involved in purine catabolism, the specific activities of 5'-nucleotidase, purine nucleosidase and xanthine dehydrogenase have been shown to be significantly higher in root nodules than in uninfected roots (7, some activity of these enzymes within this organelle.…”
mentioning
confidence: 99%
“…Evans et al (1988) isolated root-specific cDNA clones from pea and concluded that rootspecific mRNA species are present at a very low level. Fuller et al (1983) have cloned and characterized a number of nodule-specific genes. Bogusz et al (1988) isolated a haemoglobin gene expressed specifically in roots of nonnodulating plants.…”
Section: Introductionmentioning
confidence: 99%
“…A highly expressed late nodulin gene family of unknown function, the nodulin-A family, has been found in soybean (Fuller et al, 1983;Jacobs et al, 1987). The nodulin-A family comprises at least six members: Ngm-20 (Sandal et al, 1987), Ngm-23 (Mauro et al, 1985), Ngm-26b (Jacobs et al, 1987), Ngm-22/Ngm-27 (Jacobs et al, 1987;Sandal et al, 1987), Ngm-44 (Sengupta-Gopalan et al, 19861, and 15-9-A (Gottlob-McHugh and Johnson, 1991).…”
mentioning
confidence: 99%